2021
DOI: 10.1016/j.esmoop.2021.100118
|View full text |Cite
|
Sign up to set email alerts
|

Immune-inflammatory biomarkers as prognostic factors for immunotherapy in pretreated advanced urinary tract cancer patients: an analysis of the Italian SAUL cohort

Abstract: Background: Reliable and affordable prognostic and predictive biomarkers for urothelial carcinoma treated with immunotherapy may allow patients' outcome stratification and drive therapeutic options. The SAUL trial investigated the safety and efficacy of atezolizumab in a real-world setting on 1004 patients with locally advanced or metastatic urothelial carcinoma who progressed to one to three prior systemic therapies. Patients and methods: Using the SAUL Italian cohort of 267 patients, we investigated the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 47 publications
(53 reference statements)
2
53
0
Order By: Relevance
“…The median age of the patients was 61 years (IQR, 55-69). The median follow-up period was 36 months (IQR, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. In the validation cohort (Shanghai Cancer Cohort n=46), the median age of the patients was 59 years (IQR, 54-71).…”
Section: Resultsmentioning
confidence: 99%
“…The median age of the patients was 61 years (IQR, 55-69). The median follow-up period was 36 months (IQR, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. In the validation cohort (Shanghai Cancer Cohort n=46), the median age of the patients was 59 years (IQR, 54-71).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the prediction probability for patients who had no response slightly increased from 5.9–37.3% to 43.1–51.0%. To date, these inflammation indexes as prognostic biomarkers have been widely investigated in a variety of tumors, but there have been few studies on their prediction probability of agent efficacy; for example, SII at baseline could determine patients with advanced urinary tract cancer who might benefit from immunotherapy [ 29 ], and baseline NLR and LMR could predict response to first-line chemotherapy and TAS-102 + bevacizumab in advanced biliary cancer and colorectal cancer [ 30 , 31 ]. In ESCC studies, meta-analysis showed that clinical indicators such as NLR, PLR, LMR, and SII had moderate predictive ability for prognosis [ 32 ], yet their prediction ability of therapeutic efficacy, especially in relation to immunotherapy, remains rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory indices from peripheral blood have been investigated in combination with other clinical prognostic factors within prognostic models for risk-stratification in several cancer types treated with ICIs, especially the NSCLC [ 91 , 98 , 99 , 100 ]. The interest in prognostic models has also recently been increasing for genitourinary tumours, including RCC [ 101 , 102 , 103 ] and UC [ 63 , 65 , 68 , 95 , 96 , 97 , 104 ].…”
Section: Clinical Factorsmentioning
confidence: 99%
“…In patients with mUC treated with ICIs, the most frequently included factors in prognostic models are inflammatory indices (such as NLR, C-reactive protein and albumin) and pretreatment clinical parameters (i.e., the PS and metastatic site) [ 63 , 65 , 68 , 95 , 96 , 97 , 104 , 105 , 106 ]. The molecular factors included in the prognostic scores were PD-L1 expression and genomic parameters (e.g., single-nucleotide variants) [ 96 , 104 ].…”
Section: Clinical Factorsmentioning
confidence: 99%
See 1 more Smart Citation